2011
DOI: 10.1073/pnas.1019437108
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 regulates fibroblast inflammation

Abstract: Fibroblasts are important participants in inflammation. Although not leukocytes, their capacity to produce cytokines, chemokines, and other inflammatory factors locally in tissues suggests that they can contribute to inflammatory diseases. For example, fibroblasts in a rheumatoid arthritis (RA) joint are a dominant source of IL-6 and RANKL in the synovium, both of which are therapeutic targets for inflammation and bone erosion. Previously, we found that fibroblasts can be targeted by mAb directed against cadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 47 publications
2
128
1
Order By: Relevance
“…This mechanism may be related to the fact that cadherin-11 can stimulate the activation of Erk and NF-kB p65 in NR8383 macrophages. This hypothesis is consistent with a previous study that cadherin-11 directly induced cytokines, as well as activated MAPKs and the NF-kB pathway in synovial fibroblasts (40). NF-kB is a key regulator of proinflammatory cytokines, such as TNF-a and iNOS (41); both of them contribute to M1 macrophage polarization (15).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This mechanism may be related to the fact that cadherin-11 can stimulate the activation of Erk and NF-kB p65 in NR8383 macrophages. This hypothesis is consistent with a previous study that cadherin-11 directly induced cytokines, as well as activated MAPKs and the NF-kB pathway in synovial fibroblasts (40). NF-kB is a key regulator of proinflammatory cytokines, such as TNF-a and iNOS (41); both of them contribute to M1 macrophage polarization (15).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, our previous study showed that E2 potentiates proinflammatory cytokines, including TNF-a and iNOS, via NF-kB activation in the synovial membrane (11). This phenomenon may also be related to the reasons why cadherin-11 is abundantly expressed in synoviocytes and is required for synoviocytes to produce the extracellular matrix, which modulates recruitment, activation, and retention of immune cells (40). Nevertheless, further study is required to elucidate the details of the contribution of cadherin-11 to M1-like macrophage activation in inflamed joints.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged inflammatory responses further compound the problem by initiating and propagating ECM remodeling. Both integrin-and OB-cadherin-mediated signaling have been implicated in inflammation, and strategies aimed at blocking the functions of these adhesion molecules have shown preliminary success in limiting inflammation-triggered maladaptive remodeling (Chang et al, 2011;Krieglstein et al, 2002;Lee et al, 2007;Schneider et al, 2012). The overlapping and integrated networks of chemical and mechanical signals that regulate the progression of fibrotic heart disease will continue to challenge the development of promising therapies.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…It is also expressed in CFs, but the functional significance of this expression in the context of cardiac fibrosis and wound healing has not been studied. Given the known roles of OB-cadherin in inflammation and fibrosis in joint connective tissue and lungs, OB-cadherin is likely to have an important role in myocardial remodeling (Chang et al, 2011;Schneider et al, 2012 Fig. 3.…”
Section: Cadherins Sense Intercellular Forcesmentioning
confidence: 99%
“…In the healthy synovium, the FLS express Cadherin-11 (Cad-11) as the only cell type, whereas MLS express CD14 and CD68 [33,34] . First one is the detection of CD14 expression as a marker for macrophage [35], and second one the expression of CD14 with the reverse transcription polymerase chain reaction (RT-PCR). Total RNA extraction was performed using a commercial kit (SinaClon kit IRAN).…”
Section: Characterization Of Bovine Fibroblast-like Synoviocytementioning
confidence: 99%